Principles of gender-specific medicine - Legato, Marianne J., 1935-; Bilezikian, John P. (Elsevier Academic Press, 2004)
Principles of Gender-Specific Medicine examines how normal human biology differs between men and women and how the diagnosis and treatment of disease differs as a function of gender. This revealing research covers various conditions that predominantly occur in men, and as well conditions that predominantly occur in women. Among the subjects covered are cardiovascular disease, mood disorders, the immune system, lung cancer as a consequence of smoking, osteoporosis, diabetes, obesity, and infectious diseases. * Gathers important information in the field of gender-based biology and clinical medicine, proving that a patient's sex is increasingly important in preventing illness, making an accurate diagnosis, and choosing safe and effective treatment of disease * Addresses gender-specific areas ranging from organ transplantation, gall bladder and biliary diseases, to the epidemiology of osteoporosis and fractures in men and women * Many chapters present questions about future directions of investigations.